Overexpression of MiR-506 in Jurkat (Acute T Cell Leukemia) Cell Line - Rostami Yasuj, Shaghayegh (Iran J Pathol, 2020)
BACKGROUND & OBJECTIVE: Acute lymphoblastic leukemia (ALL) is a malignant disease that arises from various mutations in B or T-lymphoid progenitors. MicroRNAs (miRNAs) regulate gene expression by binding to the 3' untranslated region of protein-coding genes. Dysregulation of miRNA expression may result in the development of cancerous phenotypes. Therefore, for the first time in this field, the present study aims to investigate the effect of overexpression of miR-506 in Jurkat (acute T cell leukemia) cell line. METHODS: In this study, Jurkat cell lines were cultured in RPMI-1640 medium. Next, miR-506 was transfected with concentrations of 50 and 100 nM with Lipofectamine 2000. The accuracy of the transfection was confirmed by the transfection of siRNA conjugated with FITC. 48 h after transfection, the cells were prepared for other tests (flow cytometry, MTT assay, and RNA extraction). The expression level of miR-506 in the cells was analyzed using the quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). Finally, SPSS 21 software was used for the data analysis. RESULTS: According to our results, the viability of cells in concentrations of 50 and 100 nM was significantly higher than the control group. By overexpression of miR-506, the expressions of pro-apoptotic genes (p53, p21) and anti-apoptotic gene B-cell lymphoma-2 (BCL-2) are decreased and increased, respectively. CONCLUSION: This study showed that miR-506 may function as an oncogenic miRNA in the T- ALL cell line. In conclusion, overexpression of miR-506 leads to an increase in viable cancer cells.